Fibromuscular Dysplasia Presenting as Posterior Reversible Encephalopathy Syndrome in a Young Female - Souvik Das; Atanu Chandra (Bengal Physician Journal)
Fibromuscular dysplasia (FMD) can present with renovascular hypertension with or without hypertensive emergency in mostly young patients. A 16-year-old girl presented with uncontrolled hypertension and features of posterior reversible encephalopathy syndrome (PRES). She had no features of large vessel vasculitis. Renal artery bruit could be auscultated on the right side. Blood examination showed hyperreninemic hyperaldosteronism. The USG renal artery doppler study and invasive renal angiogram showed unilateral right renal artery stenosis. She was provisionally diagnosed as a case of FMD and was treated accordingly.